2000
DOI: 10.1021/np990456y
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive 12-Oleanene Triterpene and Secotriterpene Acids from Maytenus undata

Abstract: The aerial parts of Maytenus undata yielded four new 12-oleanene and 3,4-seco-12-oleanene triterpene acids, namely, 3-oxo-11alpha-methoxyolean-12-ene-30-oic acid (1), 3-oxo-11alpha-hydroxyolean-12-ene-30-oic acid (2), 3-oxo-olean-9(11), 12-diene-30-oic acid (3), and 3,4-seco-olean-4(23),12-diene-3, 29-dioic acid (20-epi-koetjapic acid) (5), together with the known 3, 11-dioxoolean-12-ene-30-oic acid (3-oxo-18beta-glycyrrhetinic acid) (4), koetjapic acid (6), and the 12-oleanene artifact 3-oxo-11alpha-ethoxyole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…Triterpenes are well represented in the literature (Muhammad et al, 2000) with a report of a seco-A-ring oleanene, koetjapic acid (25), from Maytenus undata (Celastraceae) (MIC; 50 and 12.5 lg/ml; SA). The seco compound is probably related to other oleananes present in the plant via a Baeyer-Villiger type oxidation (Figure 12).…”
Section: Anti-infective Natural Productsmentioning
confidence: 97%
“…Triterpenes are well represented in the literature (Muhammad et al, 2000) with a report of a seco-A-ring oleanene, koetjapic acid (25), from Maytenus undata (Celastraceae) (MIC; 50 and 12.5 lg/ml; SA). The seco compound is probably related to other oleananes present in the plant via a Baeyer-Villiger type oxidation (Figure 12).…”
Section: Anti-infective Natural Productsmentioning
confidence: 97%
“…Koetjapic acid (KA) is a seco-A-ring oleanene triterpene isolated from S. koetjape and was found to have mild cytotoxicity on a number of human cancer cell lines and murine lymphocytic leukemia (7,9). KA has been found to have anti-bacterial, anti-inflammatory, anti-tumor promoting activity and DNA polymerase inhibition properties (10)(11)(12)(13). In this study, an attempt has been made to understand the cellular and molecular mechanisms involved in cytotoxic effects of KA towards colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Since the n-hexane extract showed potential anti-proliferative activity against a breast cancer cell line, 15) it has been suggested that KA may have potential value as an anti-breast cancer agent. Accordingly, this study has been performed in order to examine the growth inhibitory effect of KA on human breast cancer cells (MCF 7), and to elucidate the mechanism(s) involved in the action of KA.…”
mentioning
confidence: 99%